2017
DOI: 10.1371/journal.pone.0187309
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the rapid spread of porcine epidemic diarrhea virus (PEDV) through an animal food manufacturing facility

Abstract: New regulatory and consumer demands highlight the importance of animal feed as a part of our national food safety system. Porcine epidemic diarrhea virus (PEDV) is the first viral pathogen confirmed to be widely transmissible in animal food. Because the potential for viral contamination in animal food is not well characterized, the objectives of this study were to 1) observe the magnitude of virus contamination in an animal food manufacturing facility, and 2) investigate a proposed method, feed sequencing, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 27 publications
0
46
0
2
Order By: Relevance
“…Rice hulls were also verified to be devoid of detectable PEDV and PDCoV genetic material. The production scale mixer used was a 0.113-m 3 electric paddle mixer (H.C. Davis Sons Manufacturing, model # SS-L1; Bonner Springs, KS) with a mix time of 5 min as described previously ( Schumacher et al, 2017 ). Feed was discharged at a rate of approximately 4.5 kg/min into a bucket elevator (Universal Industries, Cedar Falls, IA) fitted with 74 buckets (114 cm 3 each), and then discharged through a 25.4-cm diameter discharge spout and collected in plastic biohazard bags.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rice hulls were also verified to be devoid of detectable PEDV and PDCoV genetic material. The production scale mixer used was a 0.113-m 3 electric paddle mixer (H.C. Davis Sons Manufacturing, model # SS-L1; Bonner Springs, KS) with a mix time of 5 min as described previously ( Schumacher et al, 2017 ). Feed was discharged at a rate of approximately 4.5 kg/min into a bucket elevator (Universal Industries, Cedar Falls, IA) fitted with 74 buckets (114 cm 3 each), and then discharged through a 25.4-cm diameter discharge spout and collected in plastic biohazard bags.…”
Section: Methodsmentioning
confidence: 99%
“…Feed manufacturing equipment has been shown to be a potential source of porcine epidemic diarrhea virus ( PEDV ) cross-contamination ( Schumacher et al, 2017 ). Wet disinfection has been found to be the most effective feed mill equipment surface decontamination method ( Muckey, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formaldehyde-based products and an MCFA blend have been shown to reduce the presence of PEDV on these surfaces when used in conjunction with a rice hull flush. Similarly, MCFA blends have been found to be effective at reducing S. enterica serovar Typhimurium on Schumacher et al (2017) reported the role of PEDV cross-contamination in feed mills. Initially, a PEDV-negative swine diet was manufactured, followed by a diet that included an ingredient that had been spiked with infectious PEDV, then four subsequent PEDV-negative diets in an attempt to 'flush' contamination from the manufacturing surfaces.…”
Section: Addressing Feed Mills Contaminated With Biological Hazardsmentioning
confidence: 96%
“…Until the introduction of PEDV to the USA, feed for animals was not considered to be a vector in the spread of the virus. Recent studies have shown, however, that feed can be a potential vector for PEDV transmission and contaminated feed can be a source of disease (27). It is widely acknowledged that the most important risk factors for spreading the disease are contaminated vehicles (5,28).…”
Section: Transmissionmentioning
confidence: 99%